Contamination of zeolites used in oxygen production by PSA: Effects of water and carbon dioxide - J. C. Santos (2008)
Pressure swing adsorption (PSA) is one of the technologies used for producing oxygen from air. Besides the cycles employed, the adsorbent used plays an important role. Many adsorbents are nowadays available showing different adsorption properties. The adsorbent contamination that may occur in a working PSA unit has a great impact on the performance of the separation; it is then important to know the behavior of the selected adsorbent toward major contaminants such as water vapor and carbon dioxide. From the study conducted it was possible to conclude that some adsorbents are contaminated in a large extent even after being regenerated at 70 degrees C for 2 h. In this paper, the adsorption equilibrium data for several adsorbents used for oxygen production from air are presented. Oxysiv MDX and Oxysiv 7 from UOP as well as AgLiLSX from Air Products and Chemicals are shown to have very good selectivities for the separation of oxygen from air. The contamination study in a working laboratorial PSA unit packed with MS S 624 from Grace Davison is also presented. In the selected operating conditions, about 30% of the bed was contaminated.